2019
DOI: 10.1111/and.13327
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high‐fructose corn syrup consumption on testis physiopathology—The ameliorative role of melatonin

Abstract: This study investigated the ameliorative role of melatonin (MLT) and the effects of a long‐term intake of high‐fructose corn syrup (HFCS) on the male reproductive system. Thirty‐six male Sprague Dawley rats were randomly divided into 3 groups as follows: Control, HFCS and HFCS + MLT. Testis and epididymal weights were measured. Malondialdehyde (MDA) levels, superoxide dismutase (SOD) and catalase (CAT) activities, total testosterone levels, testicular histopathological damage scores were evaluated, and immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Furthermore, this dietary intervention decreased the sperm count and increased the percentage of spermatozoa with abnormal abnormal head and neck in consistence with the previous findings in highfructose-fed rats (Akarca-Dizakar et al, 2020;Aslankoc & Ozmen, 2019;Dokumacioglu et al, 2018;Meydanli et al, 2018). Our histological examination indicated that fructose intake caused testicular degeneration, evidenced by desquamation of the residual germ cells and disorganization of seminiferous tubules of the rats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, this dietary intervention decreased the sperm count and increased the percentage of spermatozoa with abnormal abnormal head and neck in consistence with the previous findings in highfructose-fed rats (Akarca-Dizakar et al, 2020;Aslankoc & Ozmen, 2019;Dokumacioglu et al, 2018;Meydanli et al, 2018). Our histological examination indicated that fructose intake caused testicular degeneration, evidenced by desquamation of the residual germ cells and disorganization of seminiferous tubules of the rats.…”
Section: Discussionsupporting
confidence: 90%
“…In a recent study, we showed that highfructose diet in rats causes an increase in inflammatory cytokines, and testicular degeneration in association with low intratesticular testosterone level, which could be related to male infertility (Yildirim et al, 2019). Previously, it was also shown that dietary fructose increases apoptotic index in seminiferous epithelial cells of rat testis producing architectural distortion, also decreases sperm count and quality (Akarca-Dizakar et al, 2020;Aslankoc & Ozmen, 2019;Dokumacioglu et al, 2018;Meydanli et al, 2018). Herein, we investigated the possible effects of dietary fructose on the testicular function, tight junction proteins, MAPK signalling and apoptotic molecules in testes of the rats to provide new insights into the causes and mechanisms of male infertility.…”
mentioning
confidence: 98%
“…As HFCS is widely used as a sweetener in various beverages and food products, its excessive consumption has become a major health issue. Intake of beverages and food products containing HFCS is associated with changes in systemic and tissue-specific metabolic status, which result in profound effects on the body, such as causing obesity 2 , insulin resistance-related and obesity-induced non-alcoholic fatty liver disease (NAFLD) 3 , cardiovascular diseases 4 , type 2 diabetes mellitus (T2DM) 5 , reproductive system diseases 6 , and even cancer 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoid is one of the most important components which is found in propolis (Tatli Seven et al, 2012). In previous studies, it was reported that oxidative damage in testicular tissue affects the reproductive system negatively and antioxidants may be able to effective in preventing or reducing this damage (Aslankoc & Ozmen, 2019;Kaya, Ciftci, Cetin, Doğan, & Başak, 2015;Tatli Seven et al, 2018). Also, it was reported that phenolic and flavonoid compounds that are especially liable for antioxidant act of propolis protected the reproductive system against to toxicity, and preventive the impacts to aluminium trichloride (AlCl 3 ) that caused corruption on testicular dysfunction, testosterone levels and semen quality (Gul Baykalir, Tatli Seven, Gur, & Seven, 2016;Ogretmen, Inanan, & Ozturk, 2014;Yousef & Salama, 2009).…”
mentioning
confidence: 99%